Giant Ocular Surface Squamous Neoplasia Wrapping Almost the Whole Cornea: A Case Report - Shrestha, Poonam; Pandey, Mukesh (Journal of Institute of Medicine Nepal, 2020)
Ocular surface squamous neoplasia (OSSN) includes the dysplastic lesions involving the epithelium of conjunctiva and cornea with various clinical pictures. Histopathological examination of the excised tissue is the benchmark for diagnosis. Surgery, chemotherapy, immunotherapy are the various treatment modalities which in combination shows promising result. We present here a case of 83 years old female patient with history of fleshy mass covering the cornea and the patient was diagnosed clinically as ocular surface squamous neoplasia. Patient underwent surgical excision of the mass followed by cryotherapy. Histopathological examination revealed conjunctival intraepithelial neoplasia of grade 3. Six months after treatment the patient is completely tumor free with no recurrence.